Image of the Man Being in Written Sources of Western Aukštaitian Subdialects of Kaunas Region: Analysis of Systemic and Textal Data - Sakalauskienė, Vilija (Vilnius University Open Series, 2020)
The article analyses the image of man in the written sources of the Western Aukštaitian subdialects of Kaunas region. The object of research is the lexeme man. The methodology of the Lublin Ethnolinguistic School and Jerzy Bartmiński was followed in the article; the works of Polish, Russian and Lithuanian ethnolinguists were also drawn on. The work is based on two types of data: systematic (dictionaries of subdialects) and textual (texts in subdialects). The material of the Western Aukštaitian subdialects of Kaunas region reveals the perception of the world by villagers and their worldview of the language. The definitions of lexicographic sources highlight three main aspects of man: physical – adult, no gender distinction; mental – intelligent, pleasant, kind, honest, serious; social – daily life related to work, relationships with other people, various communities. The study is not limited to the definitions of lexemes, but also takes into account all the data in the lexicographic entry of the word: collocations and quotations illustrating the use of the title word. The data of the lexicographic and subdialect corpus allow reconstructing the lexical semantic field of man, reflect the structure of man’s concept in discourse on subdialects, and present those features of the meaning that the representatives of the subdialect have in mind when using the word man in a specific context. According to the data in Lithuanian subdialect texts and lexicographical, man is a being capable of thinking and speaking, physically fit and healthy, honest, an obedient subordinate, working, communicating, dependent on others, his own nation or religion.